Sustainable Development of Transport as a Regional Policy Target for Sustainable Development—A Case Study of Poland - Marek Ogryzek; Ada Wolny-Kucińska (ISPRS International Journal of Geo-Information, 2021)
In central and eastern European countries that joined the European Union (EU) in 2004 and 2007, there are strong connections between transport development and sustainable regional development. The needs for transport development in post-socialist countries are so high that it is difficult to finance them, and most governments have to choose between immediate and less urgent needs. The aim of this study was to determine the role played by sustainable transport growth in the improvement of regional cohesion and sustainable regional development with a use of geographical information systems’ capabilities. The specific goals of the study were to: (i) determine the impact of EU subsidies on the regional transport development; (ii) identify threats to regional cohesion resulting from under-capitalised regions, (iii) examine geographical information systems’ capabilities in periodical regional transport development monitoring. The analyses include evaluation of the regions’ involvement in sustainable transport development as well as the presentation of direct and indirect results, such as road system improvement, with the use of GIS capabilities. It is particularly important to develop a system for monitoring the level of EU fund allocation with the use of GIS tools and the capabilities of geographic information systems. Such in-depth analysis would be useful for regional governments and decision-makers in creating and updating long term transport policies as well as monitoring long term regional development strategies. Both sustainable transport development and EU fund allocation can be monitored within the use of GIS tools, and such analyses should supplement the INSPIRE Geoportal scope.